4*(x-11)=6-x

Simple and best practice solution for 4*(x-11)=6-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4*(x-11)=6-x equation:


4*(x-11)=6-x

We simplify the equation to the form, which is simple to understand
4*(x-11)=6-x

Reorder the terms in parentheses
+(+4x-44)=6-x

Remove unnecessary parentheses
+4x-44=+6-x

We move all terms containing x to the left and all other terms to the right.
+4x+1x=+6+44

We simplify left and right side of the equation.
+5x=+50

We divide both sides of the equation by 5 to get x.
x=10

See similar equations:

| 10x+10+x=100 | | 6(2x-3)=647 | | 3n(n+3)=0 | | 2x(10)=24 | | 2x(x)=12 | | 2x(x)+1=5 | | (9x^3-5x^2+3)+(6x^2-5)=0 | | 3(x+1)=-2(x+-1)+6 | | 500x-x=1x | | 400=20e^3x | | x^2+6xy+9y^2+35=0 | | X=(3+2j)*(4+9j) | | 6(p-2)+3p=0 | | X=(3+2j)x(4+9j) | | 7x-10y=11 | | 4c+5c^2-c=0 | | 200+1000=5x | | (10-6y+e-3x)dx-2dy=0 | | lg(x+3)+lg(x-3)=lg(6) | | 8q-3+5q(2+q)=0 | | 4y-13=-5 | | 0=-k^2-4k-4 | | log(x+3)+log(x-3)=log(6) | | 5(0.8)-3p+18=(0.8+5)-2(3p-7) | | f(1.1)=1.5(1.1)+7.6 | | x^2-4x+7+5x^2-3x-6= | | 73-17=x+9answer | | 31x-10y=36 | | 2[4f+8g]= | | 7a^4(9a+6a^5)= | | x^2-5x-2x^3-5x^2+3x-2= | | 7h^4-9h^3+2h^2=0 |

Equations solver categories